Estrategia De Marketing Para Mejorar Los Niveles De Rentabilidad En La Empresa ``Gran Constructor`` De La Ciudad De Babahoyo. - Solorzano Herrera, Placida (2015)
The marketing strategy for improving levels of profitability in the company `` great constructor`` Babahoyo City, is a marketing level analysis, carried out in order to get real information and updated for relationship and the current level of customer satisfaction with the company and based on a marketing strategy that will promote the use of competitive advantages, thereby increasing the profitability of the company, increase the loyalty of existing customers and appear before the potential customers as the best option to choose; based on the problems due to the factors of distribution, marketing and segmentation, related marketing components such as the four Ps: price, product, promotion and advertising to help generate contribution to profitability. This suggests that we should promote a marketing strategy for the development of marketing and customer segmentation to focus on the competitiveness of the company.